Detecting Drivers of Behavior at an Early Age: Evidence from a Longitudinal Field Experiment - Castillo, Marco; List, John A.; Petrie, Ragan; Samek, Anya (Journal of Political Economy, 2024)
We investigate how skills developed when children are 3–5 years old drive schooling outcomes in middle childhood and adolescence. We find that skills map onto three distinct factors—cognitive skills, executive functions, and economic preferences. Importantly, each of the three factors predict later schooling outcomes. While early executive function skills and cognitive scores are linked to future behavioral patterns and other key student outcomes, economic preferences have an independent effect: children who are impatient in early childhood have more disciplinary referrals. Finally, random assignment to preschool impacts grades and disciplinary referrals through changes to cognitive skills and executive functions.